The U.S. Coptic Diaspora and the Limit of Polarization. Issue 3 (2nd July 2016) - Marzouki, Nadia
ABSTRACT: After briefly presenting the main characteristics of the Coptic diaspora in the United States and of its attempts at gaining political clout since the 1990s, the article examines the impact of the election of President Obama and of the 2011 Egyptian revolution on the rhetoric and strategy of the main Coptic organizations in the United States. I also examine the changing relation between Copts in Egypt and Copts in the United States.